Hydraulic redistribution affects modeled carbon cycling via soil microbial activity and suppressed fire. (16th May 2018) - Fu, Congsheng; Wang, Guiling; Bible, Kenneth; Goulden, Michael L.; Saleska, Scott R.; Scott, Russell L.; Cardon, Zoe G.
Abstract: Hydraulic redistribution (HR) of water from moist to drier soils, through plant roots, occurs world‐wide in seasonally dry ecosystems. Although the influence of HR on landscape hydrology and plant water use has been amply demonstrated, HR's effects on microbe‐controlled processes sensitive to soil moisture, including carbon and nutrient cycling at ecosystem scales, remain difficult to observe in the field and have not been integrated into a predictive framework. We incorporated a representation of HR into the Community Land Model (CLM4.5) and found the new model improved predictions of water, energy, and system‐scale carbon fluxes observed by eddy covariance at four seasonally dry yet ecologically diverse temperate and tropical AmeriFlux sites. Modeled plant productivity and microbial activities were differentially stimulated by upward HR, resulting at times in increased plant demand outstripping increased nutrient supply. Modeled plant productivity and microbial activities were diminished by downward HR. Overall, inclusion of HR tended to increase modeled annual ecosystem uptake of CO2 (or reduce annual CO2 release to the atmosphere). Moreover, engagement of CLM4.5′s ground‐truthed fire module indicated that though HR increased modeled fuel load at all four sites, upward HR also moistened surface soil and hydrated vegetation sufficiently to limit the modeled spread of dry season fire and concomitant very large CO2 emissions to the atmosphere. Historically, fire has been a dominant ecological force in many seasonally dry ecosystems, and intensification of soil drought and altered precipitation regimes are expected for seasonally dry ecosystems in the future. HR may play an increasingly important role mitigating development of extreme soil water potential gradients and associated limitations on plant and soil microbial activities, and may inhibit the spread of fire in seasonally dry ecosystems. Abstract : Water flow upward or downward through plant root systems, from moist to drier soil, occurs worldwide in seasonally dry ecosystems. How strongly this hydraulic redistribution (HR) affects soil microbial activities and the spread of fire remains largely unknown. Here, combined measurements and modeling showed that plant and microbial activities were stimulated by upward HR but diminished by downward HR, at times exacerbating nutrient limitation of ecosystem productivity. Modeling indicated upward HR also reduced ecosystem carbon loss through reduced fire. Although intensified soil drought is expected in the future, HR may mitigate drought's negative effects on plants, microbes, and spread of fire.